2022
DOI: 10.1158/1538-7445.sabcs21-p3-20-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-20-05: Trends of axillary treatment in sentinel node-positive breast cancer patients undergoing amputation

Abstract: Objectives: To evaluate patterns of care in axillary treatment of Dutch patients - who were diagnosed with stage I-IV primary invasive breast cancer, underwent amputation and were found positive by sentinel lymph node biopsy (SLNB) - in the years following the publication of the American College for Surgeons Oncology Group (ACOSOG)-Z0011 and After Mapping of the Axilla: Radiotherapy Or Surgery (AMAROS) trials. Methods: Data from females diagnosed between January 1st 2009 and December 31st 2018 were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our data, similar to Verreck et al, suggest that prior studies including IBCSG 23‐01, ACOSOG Z0011, and AMAROS likely have had a significant impact on the surgical management of the axilla for patients undergoing breast surgery by omitting ALNDs 8,10,12 . This trend has been described in other studies as well 19–21 . Similarly, a recent retrospective study using the NCDB (2006–2014), found that while ALND has decreased over time for mastectomy patients with positive SLNs, PMRT has increased over time 21,22 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our data, similar to Verreck et al, suggest that prior studies including IBCSG 23‐01, ACOSOG Z0011, and AMAROS likely have had a significant impact on the surgical management of the axilla for patients undergoing breast surgery by omitting ALNDs 8,10,12 . This trend has been described in other studies as well 19–21 . Similarly, a recent retrospective study using the NCDB (2006–2014), found that while ALND has decreased over time for mastectomy patients with positive SLNs, PMRT has increased over time 21,22 .…”
Section: Discussionsupporting
confidence: 85%
“…8,10,12 This trend has been described in other studies as well. [19][20][21] Similarly, a recent retrospective study using the NCDB (2006-2014), found that while ALND has decreased over time for mastectomy patients with positive SLNs, PMRT has increased over time. 21,22 Within the ALND group in our study, 44.5% underwent radiation treatment, while in the SLNB group, 38.5% underwent radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation